Peran Aplikasi Tiktok Dalam Dakwah Islam - Irwansyah Suwahyu (Referensi Islamika: Jurnal Studi Islam, 2024)
This research aims to examine the role of the TikTok application in Islamic da'wah. This research is a descriptive qualitative research where the data collection technique was obtained from the results of a questionnaire given to students of Family Welfare Education, Faculty of Engineering, UNM Class of 2023. The results of the research show that the role of the widespread TikTok application in Islamic da'wah is quite large. This is because all PKK students are users of the TikTok application. They are also active users and spend most of their free time accessing the TikTok application. On the other hand, their interest in the da'wah application on TikTok is because the time is not too long and the videos uploaded are only the main ones.